A composite material of nickel hydroxide and carbon oxide tube and its preparation method and application
Through the nickel hydroxide and carbon oxide tube composite materials as catalysts, the problem of low efficiency in electrochemical 2e-process production of hydrogen peroxide in seawater is solved, and a high selectivity and stable catalytic effect is achieved, and during dye degradation and sterilization process is achieved. Shows excellent performance.
Patent Information
- Application Number
- CN202410680593.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-05-29
AI Technical Summary
The existing electrochemical 2e-process produces hydrogen peroxide in seawater in low efficiency and lacks efficient and selective catalysts, resulting in high cost and low efficiency of the reaction system.
The nickel hydroxide and carbon oxide tube composite material are used as catalysts to treat the carbon nanotubes by concentrated nitric acid and form the nickel hydroxide and carbon oxide tube composite material in hydrothermal reaction with nickel hexahydrate to improve the activity and selectivity of the catalyst.
It achieves high selectivity for H2O2 in the range of 0 to 0.6V potentials, and the stability and efficiency of catalytic oxygen preparation of hydrogen peroxide in seawater, which reduces the cost of the reaction system and shows excellent performance in dye degradation and sterilization. performance.
Smart Images

Figure CN118651902B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material chemistry, and in particular to a nickel hydroxide and carbon oxide tube composite material and a preparation method and application thereof. Background Art
[0002] Electrochemical advanced oxidation processes based on Fenton chemistry are the most widely used advanced oxidation processes (AOPs) for the removal of persistent organic pollutants. These eco-friendly technologies have exciting advantages such as high versatility, high efficiency, strong adaptability, and good environmental compatibility, which distinguish them from other AOPs. Generally speaking, electrochemical advanced oxidation processes based on Fenton chemistry utilize in situ generated or externally added hydrogen peroxide (H2O2) to react with Fe 2+ The hydroxyl radicals produced by the Fenton reaction between ions can degrade persistent organic pollutants. - ) Direct oxygen reduction to generate H2O2 is a promising preparation method with the characteristics of reducing waste emissions, lowering energy consumption and improving safety. Therefore, the development of high 2e - Oxygen reduction-selective electrocatalysts are crucial for efficient hydrogen peroxide production.
[0003] Current electrochemical 2e - There are still many challenges in producing H2O2. Seawater resources are abundant, and using seawater to electrocatalyze oxygen to produce H2O2 can not only alleviate the problem of freshwater shortage, but also greatly reduce the processing cost of the reaction system. However, in order to improve the production efficiency of H2O2 in seawater, it is necessary to design a catalyst with high efficiency and selectivity. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end,
[0005] One object of the present invention is to provide a method for preparing a composite material of nickel hydroxide and carbon oxide tubes.
[0006] Another object of the present invention is to provide a composite material of nickel hydroxide and carbon oxide tubes prepared by the above preparation method.
[0007] Another object of the present invention is to provide an application of the composite material of nickel hydroxide and oxidized carbon tubes.
[0008] The technical solution adopted by the present invention is:
[0009] First,
[0010] The embodiment of the present invention provides a method for preparing a composite material of nickel hydroxide and carbon oxide tubes, comprising the following steps:
[0011] S1: Treat the carbon nanotubes with concentrated nitric acid, filter, wash and dry to obtain oxidized carbon nanotubes;
[0012] S2: Disperse the oxidized carbon tubes in deionized water as solution A, disperse nickel nitrate hexahydrate in deionized water as solution B, add solution B into solution A, and then add potassium hydroxide solution to carry out a hydrothermal reaction, wherein the mass ratio of the oxidized carbon tubes to the nickel nitrate hexahydrate is 10-60 mg: 0.3-1 g. After the reaction is completed, filter and dry to prepare a composite material of nickel hydroxide and oxidized carbon tubes (Ni(OH)2 / CNT).
[0013] The method of the present invention first uses concentrated nitric acid to oxidize carbon nanotubes to obtain hydrophilic oxidized carbon tubes. The oxidation treatment improves the hydrophilicity of carbon nanotubes, and the oxidized carbon tubes are more dispersed in water, increasing the surface area of adsorption. And the oxygen-containing functional groups in the oxidized carbon tubes can first adsorb nickel ions, which is convenient for adsorbing nickel hydroxide on the oxidized carbon tubes. Further, in the present invention, by controlling the reaction conditions such as the ratio of the oxidized carbon tubes and the nickel nitrate hexahydrate of the hydrothermal reaction, the nickel hydroxide in the prepared composite material is more uniformly formed into a lamellar morphology, and is compounded with the well-dispersed oxidized carbon tubes. The nickel sites in the composite material are distributed in the same layer, and are more closely combined with oxygen, and then in the subsequent test process, the OH ions in the water can be better adsorbed to generate hydrogen peroxide. The composite material has high activity and high hydrogen peroxide selectivity, and can also avoid the poisoning of chloride ions in seawater, which is conducive to the successful preparation of hydrogen peroxide in seawater.
[0014] In the embodiment of the present invention, the mass ratio of the oxidized carbon tube and the nickel nitrate hexahydrate is controlled at 10-60 mg: 0.3-1 g. The experiment found that the amount of oxidized carbon tube should not be too small. If the amount of oxidized carbon tube is too small, it will cause too little combination with the subsequent nickel hydroxide, and the conductivity of the material will deteriorate; at the same time, the amount of oxidized carbon tube should not be too much. If the amount of oxidized carbon tube is too much, it will easily agglomerate and cover the nickel hydroxide produced by the subsequent reaction, which is not conducive to the construction of active sites; the amount of nickel nitrate should not be too small. If the amount of nickel nitrate is too small, it will be not conducive to the formation of nickel hydroxide, and then the active sites will be too few; the amount of nickel nitrate should not be too much. If the amount is too much, the subsequent nickel hydroxide sheets will be piled up in large quantities, and then the activity of the composite material will be reduced.
[0015] In some embodiments, in step S1, the treatment temperature is 70-80°C, and the stirring is performed in an oil bath for 6-18 hours. More preferably, the stirring time is 10-15 hours. More preferably, the stirring time is 12 hours.
[0016] In some embodiments, in step S2, in solution A, the ratio of carbon dioxide tube to water is (10-60) mg:25 mL, preferably (25-40) mg:25 mL, and more preferably 30 mg:25 mL.
[0017] In some embodiments, in step S2, in solution B, the ratio of nickel nitrate hexahydrate to water is (0.3-1) g:5 mL, preferably (0.5-0.8) g:5 mL, and more preferably 0.73 g:5 mL.
[0018] In some embodiments, in step S2, the concentration of the potassium hydroxide solution is 1 mol / L. In step S2, the volume ratio of solution A, solution B, and potassium hydroxide solution is: 5:1:(1-9). Preferably: 5:1:(5-8). More preferably: 5:1:6. It was found in the experiment that too much or too little potassium hydroxide is not conducive to the construction of the final active site. Too little potassium hydroxide is not conducive to the formation of nickel hydroxide flakes. Too much potassium hydroxide will cause a violent reaction, and many nickel hydroxide fragments will appear in the composite material finally prepared.
[0019] As a preferred embodiment, in step S2, the mass ratio of the carbon oxide tube to the nickel nitrate hexahydrate is 30 mg:0.73 g.
[0020] In some embodiments, in step S2, the temperature of the hydrothermal reaction is 180°C and the time is 12 hours. It is found in the experiment that if the temperature is too low or the time is too short, it is not easy to form a uniform nickel hydroxide sheet, and if the temperature is too high, the reaction will be accelerated and violent, and many nickel hydroxide fragments will appear in the composite material finally prepared.
[0021] In some embodiments, in step S2, the drying temperature is 60° C. and the drying time is 5 hours.
[0022] Second,
[0023] The embodiment of the present invention further provides a nickel hydroxide and carbon oxide tube composite material, which is prepared by the above-mentioned preparation method.
[0024] In some embodiments, the nickel hydroxide of the nickel hydroxide and carbon oxide tube composite material exhibits a hexagonal flake morphology, a diameter of 50nm to 100nm, a lattice spacing of 0.236 to 0.290nm, and an R value obtained by Raman spectroscopy, that is, I D / I G ≥1.30.
[0025] Further preferably, the nickel hydroxide and carbon oxide composite material has D / I G ≥1.35. D / IG The larger it is, the more carbon defects there are and the more related reaction active sites there are, which is more conducive to improving the material's selectivity for H2O2.
[0026] Thirdly,
[0027] The embodiment of the present invention also provides a use of a composite material of nickel hydroxide and carbon oxide tubes as a catalyst in any one of the following (1) to (3):
[0028] (1) Application as a catalyst in the two-electron oxygen reduction to produce hydrogen peroxide;
[0029] (2) Application as a catalyst in the preparation of bactericidal materials;
[0030] (3) Application as a catalyst in the preparation of dye degradation materials.
[0031] In some embodiments, the nickel hydroxide and carbon oxide composite material is used as a catalyst to electrocatalyze oxygen to produce hydrogen peroxide in seawater.
[0032] Furthermore, the nickel hydroxide and carbon oxide composite material has a selectivity of more than 90% for H2O2 in the potential range of 0 to 0.6 V vs. RHE, and the H2O2 concentration is ≥10.54 g L after reacting in 1 M NaCl for 33 h. -1 .
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The nickel hydroxide and carbon oxide composite material prepared by the method of the present invention has high activity, high selectivity and durability, and excellent electrochemical performance. In the potential range of 0 to 0.6 V vs. RHE, the selectivity of the catalyst for H2O2 is more than 90%, and the H2O2 concentration is ≥10.54 g L after reacting in 1 M NaCl for 33 h. -1 , it can stably react in 1M KOH for more than 60 hours, and the cumulative concentration of H2O2 after 60 hours of reaction is ≥17.52g L -1 .
[0035] (2) The preparation process of the present invention is simple, low-cost, and easy to realize industrial production.
[0036] (3) The nickel hydroxide and carbon oxide composite material prepared by the present invention can realize the electrocatalytic production of hydrogen peroxide from oxygen in seawater.
[0037] (4) The nickel hydroxide and carbon oxide composite material prepared by the method of the present invention can effectively perform sterilization and dye degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0039] Figure 1 This is a SEM image of the nickel hydroxide and carbon oxide tube composite material (Ni(OH)2 / CNT) prepared in Example 1;
[0040] Figure 2 HRTEM image of the nickel hydroxide and carbon oxide tube composite material (Ni(OH)2 / CNT) prepared in Example 1;
[0041] Figure 3 This is a SEM image of the nickel hydroxide material (Ni(OH)2) prepared in Comparative Example 1;
[0042] Figure 4 HRTEM image of the nickel hydroxide material (Ni(OH)2) prepared in Comparative Example 1;
[0043] Figure 5 is the XRD pattern of oxidized carbon tube (O-CNT);
[0044] Figure 6 XRD diagrams of Comparative Example 1 (Ni(OH)2), Example 1 (Ni(OH)2 / CNT), Comparative Example 3 (Fe3O4 / CNT), and Comparative Example 4 (Co(OH)2 / CNT);
[0045] Figure 7 The Raman spectra of Example 1 (Ni(OH)2 / CNT) and Comparative Example 2 (NiO / CNT);
[0046] Figure 8 This is the Raman spectrum of Comparative Example 1 (Ni(OH)2);
[0047] Fig. 9 This is a SEM image of the nickel oxide and oxidized carbon tube composite material (NiO / CNT) prepared in Comparative Example 2;
[0048] Fig.10 TEM image of the nickel oxide and oxidized carbon tube composite material (NiO / CNT) prepared in Comparative Example 2;
[0049] Fig.11 This is the synchrotron radiation absorption spectrum of Example 1 (Ni(OH)2 / CNT), nickel foil, and standard nickel hydroxide;
[0050] Fig.12 LSV curves and H2O2 selectivity diagrams of Example 1 (Ni(OH)2 / CNT), Comparative Example 1 (Ni(OH)2), and Comparative Example 2 (NiO / CNT) materials in 0.1M KOH;
[0051] Fig.13 LSV curves, H2O2 selectivity and electron transfer number n of Example 1 (Ni(OH)2 / CNT), Comparative Example 1 (Ni(OH)2) and Comparative Example 2 (NiO / CNT) materials at 3.6wt.% NaCl;
[0052] Fig.14 This is a graph showing the sterilization effect of the nickel hydroxide and carbon oxide tube composite material (Ni(OH)2 / CNT) prepared in Example 1 in 15 minutes;
[0053] Fig.15 This is a dye degradation diagram of the nickel hydroxide and oxidized carbon tube composite material (Ni(OH)2 / CNT) prepared in Example 1;
[0054] Fig.16 This is a graph showing the cumulative yield of H2O2 of the nickel hydroxide and oxidized carbon tube composite material (Ni(OH)2 / CNT) prepared in Example 1 in 1 M NaCl and in 1 M KOH.
[0055] Fig.17 LSV curves and H2O2 selectivity diagrams of Example 1 (Ni(OH)2 / CNT), Comparative Example 3 (Fe3O4 / CNT), and Comparative Example 4 (Co(OH)2 / CNT) materials in 0.1M KOH, 0.9wt.% NaCl, 3.6wt.% NaCl, and 0.1MNa2SO4. DETAILED DESCRIPTION
[0056] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0057] Unless otherwise defined herein, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0058] Where values are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.
[0059] In this document, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0060] In this document, references to “preferred”, “more preferred” and “better” are merely intended to describe implementation methods or examples with better effects, and should be understood that they do not constitute limitations on the scope of protection of the present invention.
[0061] In this document, the terms “further”, “further”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0062] In this article, the term "and / or" is a description of the association relationship of objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or A and B.
[0063] As used herein, the term "about" means + / - 10%, more preferably + / - 5%, more preferably + / - 1% of the specified value.
[0064] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0065] Example 1
[0066] A method for preparing a composite material of nickel hydroxide and carbon oxide tubes (Ni(OH)2 / CNT), comprising the following steps:
[0067] (1) Weigh 2.5 g of carbon nanotubes and place them in a beaker with concentrated nitric acid. Stir in an 80°C oil bath for 12 h, with the concentrated nitric acid above the oil bath liquid level. Filter with suction, wash with deionized water until neutral, and dry at 60°C for 12 h to obtain oxidized carbon nanotubes.
[0068] (2) Weigh 30 mg of oxidized carbon tubes and disperse them in 25 mL of deionized water as solution A. Weigh 0.73 g of nickel nitrate hexahydrate and disperse them in 5 mL of deionized water as solution B. Slowly add solution B to solution A, and add 30 mL of 1 mol / L potassium hydroxide during stirring. Place the above solution in a hydrothermal autoclave and heat it at 180°C for 12 h. After the reaction is completed, filter and dry it, and dry it at 60°C for 5 h to obtain a composite material of nickel hydroxide and oxidized carbon tubes (Ni(OH)2 / CNT).
[0069] The scanning electron microscope image of the nickel hydroxide and carbon oxide tube composite material prepared in this example is as follows: Figure 1 As shown in the transmission electron microscope image Figure 2 As shown by Figure 1 , 2 It can be seen that Ni(OH)2 in the Ni(OH)2 / CNT material presents a hexagonal flake morphology with a diameter of about 50nm and is evenly dispersed on the oxidized carbon tubes.
[0070] The lattice spacing of the Ni(OH)2 / CNT sample is 0.279nm, corresponding to the (002) crystal plane, indicating that the CNT is partially inserted into the Ni(OH)2 intercalation layer, resulting in an increase in the lattice spacing of the (002) crystal plane from the original 0.230nm to 0.279nm. The selected area electron diffraction (SAED) image in the upper right corner shows that it has good crystallinity.
[0071] Figure 6 The XRD pattern of the nickel hydroxide and carbon oxide composite material prepared in this embodiment is shown. Figure 6 It can be seen that the XRD spectrum of Ni(OH)2 / CNT corresponds to the relevant crystal planes of hexagonal Ni(OH)2, 19.3° corresponds to the (001) crystal plane, 33.6° corresponds to the (100) crystal plane, 38.5° corresponds to the (101) crystal plane, 52.3° corresponds to the (012) crystal plane, 59.6° corresponds to the (110) crystal plane, and 72.8° corresponds to the (002) crystal plane. Compared with the Ni(OH)2 material of Comparative Example 1 (the 2Theta angle corresponding to the (002) crystal plane is 72.6°), the relevant 2Theta angle of the (002) crystal plane is slightly offset, which may be due to the combination with CNT.
[0072] Figure 7 The Raman spectra of Example 1 and Comparative Example 2 are shown in FIG. Figure 8 is the Raman spectrum of Comparative Example 1; and Figure 8 Raman spectrum of pure nickel hydroxide. Figure 8 The Raman spectrum of medium-purity nickel hydroxide is at 1330 cm -1 and 1560cm -1 No obvious G band and D band characteristic peaks appeared in the composite material of nickel hydroxide and oxidized carbon tubes in Example 1, while relevant characteristic peaks appeared in the composite material of nickel hydroxide and oxidized carbon tubes, which further illustrates the successful composite of nickel hydroxide and oxidized carbon tubes.
[0073] And through Figure 7 It can also be seen that the I of the Ni(OH)2 / CNT material of Example 1 D / I G is 1.35, and the I of the NiO / CNT material of Comparative Example 2 D / I G is 1.22, the carbon defects of the material in Example 1 are larger, which is more conducive to the construction of active sites, and thus the material in Example 1 has better electrochemical properties.
[0074] Fig.11 is the synchrotron radiation absorption spectra of Example 1, nickel foil (Ni foil), and standard nickel hydroxide (Std-Ni(OH)2); Fig.11 The successful synthesis of nickel hydroxide in the composite material was also further observed.
[0075] The Ni(OH)2 / CNT prepared in Example 1 was used to prepare the working electrode:
[0076] 2 mg of Ni(OH)2 / CNT prepared in Example 1 was dispersed in 990 μL of deionized water and 10 μL of 5 wt% Nafion solution by intense ultrasonic treatment (350 W, 20 min) at room temperature (~25°C) to form a catalyst ink. Then, 10 μL of the catalyst ink was dropped onto a rotating ring disk electrode (RRDE) with a theoretical collection efficiency of 37% (disk electrode area of 0.2475 cm 2 , the annular electrode area is 0.1866cm 2 ) to form a uniform catalyst layer.
[0077] Electrochemical tests were performed using the working electrode:
[0078] The electrochemical test was carried out in 0.1M KOH, or 3.6wt.% NaCl, or 1M NaCl, O2-saturated electrolyte, and the electrochemical workstation was CHI760E. The system used platinum (Pt) foil and Ag / AgCl (saturated KCl aqueous solution) as the counter electrode and reference electrode, respectively. During the entire test, the working electrode rotated at 1600r / min, and the annular electrode was set to a constant 1.5V / RHE potential to detect the generated H2O2.
[0079] Fig.12 , Fig.13 The H2O2 selectivity of the material of Example 1 in 0.1M KOH and 3.6wt.% NaCl are respectively shown. It can be seen that the selectivity of the catalyst for H2O2 can reach more than 90%.
[0080] Fig.16 This is a graph showing the cumulative yield of H2O2 from the material of Example 1 in 1M NaCl. Fig.16 It can be seen that the H2O2 yield of Ni(OH)2 / CNT material is quite constant and stable within 33 h. After 33 h of reaction in 1 M NaCl, the H2O2 concentration can reach 10.54 g L -1 , it can stably react in 1M KOH for more than 60 hours, and the cumulative concentration of H2O2 after 60 hours of reaction is ≥17.52g L -1 .
[0081] Sterilization experiment:
[0082] 30 mL of 0.9 wt% NaCl (physiological saline) was used as the electrolyte at 200 mA cm -2The disinfection effect of Staphylococcus aureus (ATCC 25923) was measured at a constant current density of 1.5 mmol / l. 450 uL electrolyte after different H2O2 accumulation tests (5 minutes, 15 minutes, 30 minutes) was mixed with 50 uL Staphylococcus aureus (10 8 CFU mL -1 ) to obtain the corresponding diluted bacterial solution (10 7 CFU mL -1 ), the diluted bacterial solution was spread on LB agar plates, and colonies were obtained after culturing for 16-20 hours. At the same time, the number of bacteria on the LB agar plates after culturing was detected or quantified, and the inhibition ratio was calculated.
[0083] Fig.14 This is a graph showing the sterilization effect of the nickel hydroxide and carbon oxide tube composite material (Ni(OH)2 / CNT) prepared in Example 1 in 15 minutes; Fig.14 It can be seen that Ni(OH)2 / CNT material can have a significant bactericidal effect within 15 minutes. Dye degradation:
[0084] The degradation process was carried out in a 1 M NaCl flow cell. Ni(OH)2 / CNT was used as the working electrode at 200 mA cm -2 After 20 minutes of accumulation test, 30 mL of 50 mg L -1 Rhodamine B and methylene blue solutions were added to 30 mL of cathode tank electrolyte, mixed thoroughly, and decomposed under sunlight. The concentration ratio curve was obtained by measuring the UV-visible adsorption intensity. The dye degradation test was carried out in 1M NaCl solution without H2O2, with UV irradiation as a control.
[0085] Fig.15 The dye degradation diagram of the nickel hydroxide and oxidized carbon tube composite material (Ni(OH)2 / CNT) prepared in Example 1; - -ORR and UV synergistic effect, rhodamine B completely faded in about 15min, methylene blue completely faded in 90min, the degradation rate exceeded 97%. The control test had no obvious effect on inducing dye degradation.
[0086] Comparative Example 1
[0087] Nickel hydroxide material, denoted as Ni(OH)2, the steps are as follows:
[0088] Weigh 0.73 g of nickel nitrate hexahydrate and disperse it in 5 mL of deionized water, add 30 mL of 1 mol / L potassium hydroxide during stirring. Put the above solution in a hydrothermal kettle and heat it at 180°C for 12 hours. After the reaction is completed, filter and dry it at 60°C for 5 hours to obtain nickel hydroxide material.
[0089] The scanning electron microscope image of the nickel hydroxide material prepared in this comparative example is as follows Figure 3 As shown, the prepared material is relatively uniform, with a diameter of about 50 nm, but it will aggregate together to form lumps.
[0090] The HRTEM of the nickel hydroxide material prepared in this comparative example is as follows Figure 4 As shown in Figure 2, the Ni atoms in the Ni(OH)2 crystal are arranged in an orderly manner. It is worth noting that nickel vacancies and structural defects are generated during the hydrothermal process. The lattice spacing is 0.230nm, which corresponds to the spacing of Ni(OH)2(002).
[0091] The electrochemical performance of the material of Comparative Example 1 was characterized using the same electrochemical test as Example 1.
[0092] pass Fig.12 It can be seen that the material prepared in this comparative example has a selectivity of 79.2% for H2O2 in KOH electrolyte within the potential range of 0 to 0.6 V vs. RHE. Fig.13 It can be seen that in the 3.6wt.% NaCl electrolyte, the selectivity for H2O2 is 91% in the potential range of -0.3 to 0.2V vs. RHE, but Fig.13 It can be seen from the LSV curve that the ring current and disk current of the material are relatively low, so the activity of the material is poor. Although the selectivity of H2O2 is high, the ability of H2O2 to accumulate over a long period of time is average.
[0093] Comparative Example 2
[0094] The nickel oxide and carbon oxide tube composite material, referred to as NiO / CNT, is prepared by the following steps:
[0095] (1) Weigh 2.5 g of carbon nanotubes and place them in a beaker with concentrated nitric acid. Stir in an oil bath at 80°C for 12 h, with the concentrated nitric acid above the level of the oil bath. Filter, wash with deionized water until neutral, and dry to obtain oxidized carbon nanotubes.
[0096] (2) Weigh 30 mg of carbon dioxide tubes and disperse them in 25 mL of deionized water as solution A, weigh 0.73 g of nickel nitrate hexahydrate and disperse them in 5 mL of deionized water as solution B, slowly add solution B to solution A, and add 30 mL of 1 mol / L potassium hydroxide during stirring. Place the above solution in a hydrothermal autoclave and heat it at 180°C for 12 h. After the reaction is completed, filter and dry it, and dry it at 60°C for 5 h to obtain a composite material of nickel hydroxide and carbon dioxide tubes.
[0097] (3) The nickel hydroxide and carbon oxide composite material prepared in step (2) was ventilated in argon for 2 hours and heated at 500° C. for 2 hours.
[0098] The scanning electron microscope image of the nickel oxide and carbon oxide composite material prepared in this comparative example 2 is as follows: Fig. 9 As shown, it can be seen that nickel oxide appears in flakes of varying sizes, but is tightly combined with carbon oxide tubes and is dispersed more evenly.
[0099] The TEM image of the nickel oxide and carbon oxide composite material prepared in Comparative Example 2 is as follows: Fig.10 As shown, the lattice spacing is 0.209 nm, corresponding to the distance of NiO / CNT (200). It is worth noting that structural defects are generated during the hydrothermal process.
[0100] The electrochemical performance of the material of Comparative Example 2 was characterized using the same electrochemical test as Example 1.
[0101] pass Fig.12 It can be seen that the material prepared in this comparative example has a selectivity of 78.4% for H2O2 in KOH electrolyte within the potential range of 0 to 0.6 V vs. RHE; Fig.13 It can be seen that in 3.6 wt.% NaCl electrolyte, the selectivity for H2O2 is 72.6% in the potential range of -0.3 to 0.2 V vs. RHE.
[0102] Comparative Example 3
[0103] The composite material of ferroferric oxide and carbon oxide tubes, denoted as Fe3O4 / CNT, has the following steps:
[0104] (1) Weigh 2.5 g of carbon nanotubes and place them in a beaker with concentrated nitric acid. Stir in an oil bath at 80°C for 12 h, with the concentrated nitric acid above the level of the oil bath. Filter, wash with deionized water until neutral, and dry to obtain oxidized carbon nanotubes.
[0105] (2) Weigh 30 mg of oxidized carbon tubes and disperse them in 25 mL of deionized water as solution A, weigh 0.70 g of ferrous sulfate and disperse them in 5 mL of deionized water as solution B, slowly add solution B to solution A, and add 30 mL of 1 mol / L potassium hydroxide during stirring. The above solution is placed in a hydrothermal autoclave and heated at 180°C for 12 h. After the reaction is completed, filter and dry, and dry at 60°C for 5 h to obtain a composite material of ferric hydroxide and oxidized carbon tubes (Fe(OH)3 / CNT).
[0106] (3) The iron hydroxide and carbon oxide tube composite material prepared in step (2) was ventilated in argon for 2 hours, and heated at 500° C. for 2 hours to finally obtain the iron oxide and carbon oxide tube composite material.
[0107] Figure 6 The XRD pattern of the composite material of Comparative Example 3 is shown. Figure 6It can be seen that the ferroferric oxide and carbon oxide tubes are successfully compounded.
[0108] The electrochemical performance of the material of Comparative Example 3 was characterized by the same electrochemical test as Example 1.
[0109] Comparative Example 4
[0110] The cobalt hydroxide and carbon oxide tube composite material, denoted as Co(OH)2 / CNT, is prepared by the following steps:
[0111] (1) Weigh 2.5 g of carbon nanotubes and place them in a beaker with concentrated nitric acid. Stir in an oil bath at 80°C for 12 h, with the concentrated nitric acid above the level of the oil bath. Filter, wash with deionized water until neutral, and dry to obtain oxidized carbon nanotubes.
[0112] (2) Weigh 30 mg of oxidized carbon tubes and disperse them in 25 mL of deionized water as solution A, weigh 0.73 g of cobalt nitrate hexahydrate and disperse them in 5 mL of deionized water as solution B, slowly add solution B to solution A, and add 30 mL of 1 mol / L potassium hydroxide during stirring. The above solution is placed in a hydrothermal autoclave and heated at 180°C for 12 h. After the reaction is completed, filter and dry, and dry at 60°C for 5 h to obtain a composite material of cobalt hydroxide and oxidized carbon tubes (Co(OH)2 / CNT).
[0113] Figure 6 The XRD pattern of the composite material of Comparative Example 4 is shown. Figure 4 It can be seen that cobalt hydroxide and carbon oxide tubes are successfully composited.
[0114] The electrochemical performance of the material of Comparative Example 4 was characterized using the same electrochemical test as Example 1.
[0115] Fig.12 The LSV curves and H2O2 selectivity diagrams of Example 1 (Ni(OH)2 / CNT), Comparative Example 1 (Ni(OH)2), and Comparative Example 2 (NiO / CNT) in 0.1M KOH; Fig.12 It can be seen that the current density of Ni(OH)2 / CNT, Ni(OH)2, and NiO / CNT materials is relatively large, which is very conducive to the production of H2O2 in 0.1M KOH electrolyte. At the same time, the H2O2 selectivity of the nickel hydroxide carbon tube composite material is above 90% as a whole, averaging 92.7% under the voltage window of 0-0.7V vs.RHE, the selectivity of NiO / CNT material is 78.4%, and the selectivity of Ni(OH)2 material is 79.2%, which is less than 80% as a whole. Compared with Ni(OH)2 and NiO / CNT materials, the Ni(OH)2 / CNT material of the present invention has better H2O2 selectivity in an alkaline environment and can produce H2O2 well.
[0116] Fig.13 Figure 1 is the LSV curve, H2O2 selectivity and electron transfer number n of Example 1 (Ni(OH)2 / CNT) and Comparative Example 1 (Ni(OH)2) and Comparative Example 2 (NiO / CNT) materials at 3.6wt.% NaCl; the ring current of Ni(OH)2 / CNT material at 3.6wt% NaCl is significantly higher than that of the other two comparative samples Ni(OH)2 and NiO / CNT. Fig.13 In the right figure, although the H2O2 selectivity of Ni(OH)2 material is higher than that of Ni(OH)2 / CNT material, the ring current and disk current of nickel hydroxide material are relatively small. According to formula (1),
[0117]
[0118] Among them I r and I d are the ring current and disk current respectively, and N is the collection efficiency (N=0.37).
[0119] Therefore, when the ring current and disk current are both low, there will be a situation where the H2O2 selectivity is high. However, under the same conditions, the effect of Ni(OH)2 material in producing H2O2 is far less than that of Ni(OH)2 / CNT material. The reason for this is that Ni(OH)2 material does not contain CNT, while oxidized carbon tubes can provide some conductivity; from the morphology of NiO / CNT material, nickel oxide agglomerates together and buries part of the carbon tubes, resulting in a decrease in conductivity. Figure 7 It can also be seen from the Raman image that the I D / I G It is smaller than Ni(OH)2 / CNT material, which indicates that it has fewer defects and related reaction active sites, thus having poor selectivity.
[0120] Fig.17 The LSV curves and H2O2 selectivity diagrams of Example 1 (Ni(OH)2 / CNT), Comparative Example 3 (Fe3O4 / CNT), and Comparative Example 4 (Co(OH)2 / CNT) materials in 0.1M KOH, 0.9wt.% NaCl, 3.6wt.% NaCl, and 0.1M Na2SO4. The GCD in the figure is a blank sample. Fig.17It can be seen that the ring current and H2O2 selectivity of Ni(OH)2 / CNT material under the conditions of 0.1M KOH, 0.9wt% NaCl, 3.6wt% NaCl and 0.1M NaSO4 are significantly higher than those of Fe3O4 / CNT material, Co(OH)2 / CNT material and GCD. The selectivities in four different electrolytes are 92.7%, 91.8%, 93.4% and 88.5%, respectively, which are significantly higher than 72.0%, 88.1%, 87.7%, 76.4% of GCD and 64.6%, 56.5%, 53.6%, 38.4% of Fe3O4 / CNT and 69.3%, 41.4%, 49.4%, 47.9% of Co(OH)2 / CNT. The reasons may be: first, the Fe3O4 / CNT material embeds active sites, and second, iron is more inclined to form a four-electron oxygen reduction reaction during the oxygen reduction reaction, so the hydrogen peroxide selectivity of this material is poor. Although cobalt in other systems such as cobalt-nitrogen coordination structures tends to be two-electron oxygen reduction, in Co(OH)2 / CNT, the cobalt-oxygen coordination structure is more inclined to form a four-electron oxygen reduction process, so the hydrogen peroxide selectivity of this material is also poor; at the same time, the cobalt site is difficult to resist the poisoning of chloride ions, so the overall level shows a low hydrogen peroxide selectivity. The Ni(OH)2 / CNT material of this application is coated on GCD, has high activity, high hydrogen peroxide selectivity, and can avoid chloride ion poisoning in seawater. It can have good current and high H2O2 selectivity in all electrolytes.
[0121] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0122] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. Use of a composite material of nickel hydroxide and carbon oxide tubes as a catalyst in any of the following (1) to (3): (1) Application as a catalyst in the two-electron oxygen reduction to produce hydrogen peroxide; (2) Application as a catalyst in the preparation of bactericidal materials; (3) Application as a catalyst in the preparation of dye degradation materials; The nickel hydroxide and carbon oxide tube composite material is prepared by a method comprising the following steps: S1: Treat the carbon nanotubes with concentrated nitric acid, filter, wash and dry to obtain oxidized carbon nanotubes; S2: dispersing the oxidized carbon tubes in deionized water as solution A, dispersing nickel nitrate hexahydrate in deionized water as solution B, adding solution B to solution A, and then adding potassium hydroxide solution to carry out a hydrothermal reaction, wherein the mass ratio of the oxidized carbon tubes to the nickel nitrate hexahydrate is 10-60 mg: 0.3-1 g, and after the reaction is completed, filtering and drying to prepare a composite material of nickel hydroxide and oxidized carbon tubes; in, In step S1, the treatment temperature is 70-80°C, and the mixture is stirred in an oil bath for 6-18 hours; In step S2, in solution A, the ratio of carbon dioxide tube to water is (10~60) mg:25 mL, the ratio of nickel nitrate hexahydrate to water is (0.3~1) g:5 mL, the concentration of the potassium hydroxide solution is 1 mol / L, and in step S2, the volume ratio of solution A, solution B, and potassium hydroxide solution is: 5:1:(1~9).
2. The use according to claim 1, characterized in that: The nickel hydroxide and carbon oxide tube composite material is used as a catalyst to realize electrocatalytic oxygen production of hydrogen peroxide in seawater.
3. The use according to claim 1, characterized in that: The nickel hydroxide and carbon oxide composite material has a selectivity of more than 90% for H2O2 in the potential range of 0-0.6 V vs. RHE, and the H2O2 concentration is ≥10.54 g L-1 after reacting in 1 M NaCl for 33 h. -1 .
4. The use according to claim 1, characterized in that: In step S1, the mixture is stirred under an oil bath for 10 to 15 h.
5. The use according to claim 4, characterized in that: In step S1, the mixture was stirred under oil bath for 12 h.
6. The use according to claim 1, characterized in that: In step S2, in solution A, the ratio of carbon dioxide tube to water is (25-40) mg: 25 mL; in solution B, the ratio of nickel nitrate hexahydrate to water is (0.5-0.8) g: 5 mL; and the volume ratio of solution A, solution B, and potassium hydroxide solution is 5:1:(5-8).
7. The use according to claim 6, characterized in that: In step S2, in solution A, the ratio of carbon dioxide tube to water is 30 mg:25 mL; in solution B, the ratio of nickel nitrate hexahydrate to water is 0.73 g:5 mL; and the volume ratio of solution A, solution B, and potassium hydroxide solution is 5:1:
6.
8. The use according to claim 6 or 7, characterized in that: In step S2, the temperature of the hydrothermal reaction is 180° C. and the time is 12 h.
9. The use according to any one of claims 1 to 3, characterized in that: The nickel hydroxide of the nickel hydroxide and carbon oxide tube composite material presents a hexagonal flake morphology, a diameter of 50nm-100nm, a lattice spacing of 0.236-0.290nm, and an R value obtained by Raman spectroscopy, that is, I D / I G ≥1.
30.
10. The use according to claim 9, characterized in that: The nickel hydroxide and carbon oxide tube composite material I D / I G ≥1.35.
Citation Information
Patent Citations
Nanofiber-shaped three-dimensional nickel hydroxide / carbon nanotube composite material as well as preparation method and application thereof
CN104021948A
Beta-cobalt nickel hydroxide and nickel plated carbon nanotube composite material and preparation method and application thereof
CN105551818A
Beta-nickel hydroxide-multiwall carbon nanotube / unsaturated polyester resin nano composite flame-retardant material and preparation method of material
CN107586442A
Preparation method and application of nickel hydroxide / nickel oxide nickel-containing carbon nanofiber composite material
CN115527784A
Transition metal / carbon nanotube composite and method of preparing the same
US20100181200A1
